Smaller right amygdala in Caucasian alcohol-dependent male patients with a history of intimate partner violence: a volumetric imaging study - Zhang, Lishu; Kerich, Mike; Schwandt, Melanie L.; Rawlings, Robert R.; McKellar, Joshua D.; Momenan, Reza; Hommer, Daniel W.; George, David T. (Addiction biology, 2013)
ABSTRACT Studies have shown that various brain structure abnormalities are associated with chronic alcohol abuse and impulsive aggression. However, few imaging studies have focused on violent individuals with a diagnosis of alcohol dependence. The present study used volumetric magnetic resonance imaging (MRI) to compare the volumes of different structural components of prefrontal cortex and six subcortical structures in perpetrators of intimate partner violence with alcohol dependence (IPV‐ADs), non‐violent alcohol‐dependent patients (non‐violent ADs) and healthy controls (HCs). Caucasian men (n = 54), ages 24–55, who had participated in National Institutes of Alcohol Abuse and Alcoholism treatment programs, were grouped together as IPV‐ADs (n = 27), non‐violent ADs (n = 14) and HCs (n = 13). The MRI scan was performed at least 3 weeks from the participant's last alcohol use. T1‐weighted images were used to measure the volumes of intracranial space, gray and white matter, orbitofrontal cortex, medial prefrontal cortex, lateral prefrontal cortex, and six subcortical structures. Results revealed that IPV‐ADs, compared with non‐violent ADs and HCs, had a significant volume reduction in the right amygdala. No significant volumetric difference was found in other structures. This finding suggests that structural deficits in the right amygdala may underlie impulsive types of aggression often seen in alcohol‐dependent patients with a history of IPV. It adds to a growing literature suggesting that there are fundamental differences between alcohol‐dependent patients with and without IPV.